Can a-C:H-Sputtered Coatings Be Extended to Orthodontics? - Frois, António (2021)
Hydrogenated amorphous carbon (a-C:H) coatings are attractive materials for protecting metallic surfaces in extreme biological environments like the human oral cavity, due to the unusual combination of mechanical properties, superior bioinertness, and relative easier and cheaper produc-tion. In this work, two a-C:H coatings were deposited on AISI 316L substrates by reactive magnetron sputtering with two CH4 flows to assess if this outstanding system could extend its application range to orthodontics. A 30-day immersion test in Fusayama-Meyer artificial saliva was conducted to mimic an extreme acidic intraoral pH. Extracts were quantified and used to perform in vitro assays with mono-and co-cultures of macrophages and fibroblast to assess cell viability, while mechanical and structural behaviors were studied by nanoindentation and visible Raman. The empirically estimated H contents of ~28 and 40 at.% matched the hard and soft a-C:H coating regimes of 18 and 7 GPa, respectively. After immersion, no important structural/mechanical modifications occurred, regard-less of the H content, without corrosion signs, delamination, or coating detachment. However, the adhesion-promoting Cr-based interlayer seems to reduce corrosion resistance via galvanic coupling. The highest biocompatibility was found for a-C:H coatings with the lowest H content. This study indicates that sputtered a-C:H are promising surface materials in orthodontics.